(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Our old poetry is still attracting us by its meaning, structure and pectorial methods, and it opens up in front of us prospects of study and research. How much the researchers studied its solid peaks, and they are still discovering in its hidings a lot and new things. When ever they read deeply and they saild in its hidden and mysterious waves, and our heritage is rich with the poetry of unknown poets who are still forgetten for many reasons. Giran Al-oud Al-Numyrie is one of the poets who didn’t write largely which we stopped to study them, and his poetry drew our attention by its different subjects. What was found of the distinct technical and rhetorical properties, and the poetry for woman drew our attention, He was a poet of flirtation and description by describing woman excessively. He succeeded in portraiting the woman and he had his own experience with her. We wanted to remove what is unknown a bout this poet, and his life and stop to think a bout the woman in his poetry. We can discern the variety of photos discriptions which he presented for the woman, and we can feed the effect of environment and Culture and his personal life of the poet in riching his poetic experience and nourishing his imagination .